A-t-on le droit de rigoler bêtement en France ?L’évaluation (trop) sérieuse des comédies de Will Ferrell - Antoine Gaudé (Mise au Point)
Examining Will Ferrell’s unpopularity in France, through a reception study, means considering humor as a cultural and sociological phenomenon. Will Ferrell is indubitably not the only actor in the history of American comedy to be at the same time well-loved in the US and overlooked in France (Chevy Chase, John Candy, etc.), but he is probably the case where the difference of opinion is the most extreme. This article will analyze the press, the criticism, and Internet forums, as ways to understand the social and cognition construction of the evaluation of the 54-year-old comedian’s movies. Laughter, more than any other cinematic pleasure, is transcultural and transnational. However, the viewer’s visual culture evolves and is enriched, and comic modes can change, depending on film techniques and cultural contexts of production and reception. This reception study will focus on the rhetoric of French spectators, the construction of their personal views, the different communities into which they are divided, and their exchanges.